Kajian Kemampuan Membaca Permulaan Siswa Kelas I SDN 38 Sungai Ambawang - Marlinda, Marlinda; Afryaningsih, Yunika; Listiarini, Yuni (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the initial reading ability of grade 1 students of SDN 38 Sungai Ambawang. This type of research uses a qualitative approach. The data collection technique in this study uses the EGRA test. The researcher used the EGRA test in assessing the initial reading ability of grade 1 students of SDN 38 Sungai Ambawang. The EGRA test consists of five aspects, namely knowing letters, reading words, reading words that have no meaning, fluency in reading aloud and comprehension of reading and listening (listening comprehension). The results of the study showed that the ability of grade 1 students of SDN 38 Sungai Ambawang in the aspect of recognizing letters was 77%, of which 5 out of 15 students were still unable to recognize letters. The aspect of word reading resulted from the average ability of students was 69%, of which 6 out of 15 students were found to be in the good to very good category in word reading. The aspect of reading words has no meaning found that 7 out of 15 students are still not good at reading words that do not mean the average score of the whole student, which is 60%. The aspects of fluency in reading aloud and comprehension were found as many as 7 out of 15 students were less able in reading aloud and reading comprehension, their average score was 60%. The aspect of listening (listening comprehension) was found as many as 7 out of 15 students who were not completely good at answering questions given by the researcher about the reading, read with an average score of 63% of their ability